Species selection and driven mechanisms jointly generate a large-scale morphological trend in monobathrid crinoids. Issue 3 (8th April 2010) - Simpson, Carl
Abstract : All evolution attributable to natural selection, at any level, is due to a causal covariance between fitness and phenotype. Over macroevolutionary time scales, species selection is one of many possible mechanisms for generating large-scale morphological trends. For species selection to sort morphology, a correlation between morphology and taxonomic diversification rate must be present. Other trend mechanisms (driven mechanisms, e.g., a bias in the direction of speciation) produce a systematic change in the mean phenotype over time. All mechanisms can co-occur. Here I demonstrate (1) an inverse correlation between diversification rate and calyx complexity that demonstrates the effect of species selection on morphology. Genera with simple calyces tend to increase in diversity, whereas genera with complex calyces have a net decrease in diversity; and (2) the presence of a driven trend mechanism in monobathrid crinoids where descendant genera tend to be simpler than their ancestors. The separate effects of these two classes of trend mechanisms can be combined by using the Price's Theorem, which partitions the contribution to the overall change in calyx complexity over time accurately among selection and driven mechanisms. Price's Theorem provides significant conceptual and methodological clarification of the contribution of multiple and interacting hierarchical mechanisms in generating large-scale trends.